2013
DOI: 10.1080/14703297.2012.748333
|View full text |Cite
|
Sign up to set email alerts
|

Engaging students with feedback through adaptive release

Abstract: Feedback to students has been highlighted in the literature as an area where improvements are needed. Students need high quality, prompt feedback, but they also need guidance and tools to help them engage with and learn from that feedback. This case study explores staff and student perceptions of a tool at Sheffield Hallam University which releases electronic feedback to students before allowing them to access their grades. This approach was designed to encourage feedback engagement and connection with future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…It's possible that some students focus more on the positive comments than those which are perceived as negative, or believe, for example, that if a substantial degree of effort put into the work has been recognised by the marker, that this must automatically equate to a high grade. Nevertheless, a slight majority were in favour of withholding the grade, and their comments indicated that grade withholding encouraged them to analyse the feedback more carefully, in line with the findings of others (Irwin et al, 2013). …”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…It's possible that some students focus more on the positive comments than those which are perceived as negative, or believe, for example, that if a substantial degree of effort put into the work has been recognised by the marker, that this must automatically equate to a high grade. Nevertheless, a slight majority were in favour of withholding the grade, and their comments indicated that grade withholding encouraged them to analyse the feedback more carefully, in line with the findings of others (Irwin et al, 2013). …”
Section: Discussionsupporting
confidence: 52%
“…The changes in our approaches to implementing the reflections in 2013-14, and increased emphasis on generation of active action plans, may have facilitated the acquisition of the requisite skills in effective use of feedback in a proportion of the class for whom feedback may otherwise have had little positive effect. It is evident from our own experience that not all students immediately grasp the concept of reflecting on feedback, as has also been reported by Irwin et al (2013). The step of reviewing student reflections as an integral part of the overall process is clearly important in order to provide guidance in relation to the reflection and the action plans that are generated.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, this design could have unintended negative consequences for student access to feedback in LMS, especially if students are primarily focused on obtaining their assessment scores (eg, Nesbit & Burton, ; Winter & Dye, ) or alternatively, if they exhibit strong emotional responses to marks that might influence their motivation to view feedback (Carless, ). To encourage engagement with feedback and reduce the focus on marks, some researchers advocate for a “feedback first, marks second” approach and have developed software that releases feedback files prior to marks in LMS (“adaptive release,” Irwin, Hepplestone, Holden, Parkin, & Thorpe, ; Parkin et al , ). In contrast, when students are required to open a separate feedback file after receiving their marks, this could be interpreted as a “marks first, feedback second” approach.…”
Section: Introductionmentioning
confidence: 99%